Neural mechanism underlies CYLD modulation of morphology and synaptic function of medium spiny neurons in dorsolateral striatum - Tan, Shu-yi; Jiang, Jin-xiang; Huang, Hui-xian; Mo, Xiu-ping; Feng, Jing-ru; Chen, Yu; Yang, Li; Long, Cheng (Frontiers in Molecular Neuroscience, 2023)
Although the deubiquitinase cylindromatosis (CYLD), an abundant protein in the postsynaptic density fraction, plays a crucial role in mediating the synaptic activity of the striatum, the precise molecular mechanism remains largely unclear. Here, using a Cyld-knockout mouse model, we demonstrate that CYLD regulates dorsolateral striatum (DLS) neuronal morphology, firing activity, excitatory synaptic transmission, and plasticity of striatal medium spiny neurons via, likely, interaction with glutamate receptor 1 (GluA1) and glutamate receptor 2 (GluA2), two key subunits of alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs). CYLD deficiency reduces levels of GluA1 and GluA2 surface protein and increases K63-linked ubiquitination, resulting in functional impairments both in AMPAR-mediated excitatory postsynaptic currents and in AMPAR-dependent long-term depression. The results demonstrate a functional association of CYLD with AMPAR activity, which strengthens our understanding of the role of CYLD in striatal neuronal activity.